Vascular endothelial growth factor D is a biomarker of fluid overload in haemodialysis patients. Issue 3 (10th January 2020) - von Moos, Seraina; Segerer, Stephan; Davenport, Andrew; Sadoune, Malha; Gerritsen, Kerem; Pottecher, Julien; Ruschitzka, Frank; Mebazaa, Alexandre; Arrigo, Mattia; Cippà, Pietro E
Abstract: Background: Improved understanding and assessment of the complex physiology of volume regulation in haemodialysis (HD) patients are required to improve patient care and reduce mortality associated with fluid overload (FO). Methods: We searched for FO-related biomarkers among 184 peptides associated with cardiovascular disease in a cohort of 30 HD patients. First, we assessed the direct impact of HD on the peptides of interest by comparing plasma concentrations before and after treatment. Then, we compared cardiovascular peptide profiles between patients with and without FO as defined by bioimpedance analysis (BIA). The plasma concentration of selected candidate biomarkers for FO was determined by enzyme-linked immunosorbent assay (ELISA) and correlated with previously described FO-related clinical and laboratory parameters. For validation, results were confirmed in an independent cohort of 144 HD patients. Results: We found seven peptides positively [NT-proBNP, B-type natriuretic peptide (BNP), vascular endothelial growth factor D (VEGFD), tumour necrosis factor-related apoptosis-inducing ligand receptor 2, growth differentiation factor 15, tumour necrosis factor ligand superfamily member 13B, chitinase-3-like protein 1] and five negatively (leptin, renin, epidermal growth factor receptor, interleukin-1 receptor antagonist, myeloblastin) correlated to FO. In addition to natriuretic peptides, VEGFD emerged as third peptide highly correlated with BIA (ρ = 0.619, P < 0.0001). In line with this, VEGFD concentration verified by ELISA correlated with BIA, BNP and soluble CD146 but not with vascular endothelial growth factor C (VEGFC). Notably, levels of VEGFD were unrelated to cardiac systolic function (P = 0.63), contrary to BNP (P = 0.0003). Finally, we observed that 1-year all-cause mortality was higher in patients with high BNP (P = 0.0002), FO (defined by BIA, P = 0.04) and high VEGFD (P = 0.02), but not with high VEGFC (P = 0.48). Conclusion: VEGFD is a novel FO-related biomarker with unique diagnostic and prognostic properties.